What determines the ‘culture of silence’? Disclosing and reporting sexual harassment among university employees and students at a large Swedish public university - Per-Olof Östergren; Catarina Canivet; Ulrika Andersson; Anette Agardh (PLoS ONE, 2025)
Background The MeToo-movement challenges the ‘culture of silence’ regarding sexual harassment (SH). There are few studies regarding this phenomenon in academic settings. The aim of this study was to investigate the relationship between having reported or disclosed SH, on the one hand, and background factors and general health and wellbeing of exposed individuals, types of SH and perpetrator characteristics, on the other hand. Methods and results A questionnaire sent to all employees and students at a large Swedish university was returned by 33% (N = 2736) and 32% (N = 9677), respectively. This study is based on the 469 employees and 2044 students who affirmed that they had been exposed to SH at the university. Analyses were made by means of chi2 tests and logistic regression. Among employees, 38.8% had disclosed, i.e., talked to someone at the university about their experience, and 17.3% had formally reported, i.e., talked to someone at the university who had the obligation to act on this information. The corresponding figures among students were 11.2% and 4.0%. A higher professional rank was linked to lower disclosing and reporting behavior, although not statistically significantly. Among students, exposure to attempted or completed rape was linked to low rates of disclosing (24.3%) and reporting (8.1%). An asymmetrical power relationship was associated with higher rates of disclosing and reporting; although statistically significant for reporting only among employees, and for disclosing only among students. None of the health-related outcomes were related to disclosing or reporting. Conclusions The study confirmed a culture of silence regarding SH in the university setting. Several factors were linked to this, which can be associated with gendered and other power relations in society at large and in the academic setting in particular. Similar factors affected employees as well as students, but the culture of silence seemed more pronounced among students.